Collective Kiai Leadership Policies in Enhancing Madrasah Quality at Bahrul Ulum Islamic Boarding School Tambakberas Jombang - HM. Adibussholeh; Ahmad Tanzeh; Akhyak Akhyak (International Journal of Islamic Educational Research, 2026)
This study aims to analyze the collective kiai leadership policies in enhancing the quality of madrasah education at Bahrul Ulum Islamic Boarding School, Tambakberas, Jombang. Using a qualitative research method with a phenomenological approach, the study collects data through in-depth interviews, structured observation, and documentation. The data analysis process involves three stages: data condensation, data display, and conclusion drawing. The study reveals that the formulation of collective leadership policies is based on the need to achieve religious goals, legal foundations, and community needs. These policies are oriented toward problem-solving and continuity, formulated through deliberation and consensus involving all kiai leaders of both formal and non-formal educational institutions within the pesantren. The implementation of these policies emphasizes scholarly sanad and intellectual tradition across all educational institutions. Key aspects include educational administration, human resource development, strengthening formal education based on national accreditation standards, providing entrepreneurship education, and participating in faith-based as well as science and technology competitions at national and international levels. The evaluation of these policies is carried out collectively by all caretakers and leaders in alignment with established policies to ensure quality improvement across the pesantren’s formal and non-formal educational institutions.